ANALISIS KONTRASTIF BENTUK VERBA BAHASA INGGRIS DAN BAHASA INDONESIA BERDASARKAN KALA DAN JUMLAH DALAM BERITA BBC DWI BAHASA (KAJIAN LINGUISTIK KONTRASTIF DAN PENERJEMAHAN) - S.S., M.M., M.Hum., Tri Pujiati, (Jurnal Sasindo UNPAM, 2015)
The research entitled â€œContrastive Analysis of English and Indonesian Verb Based on Tenses and Numbers on BBC Bilingual (Study of Contrastive Linguistics and Translation). This research to contrast the verb form of English language and Indonesian language based on contrastive analysis. The researcer limits the study only on verb form based on tense, number, and also the equivalence of translation. This research using descriptive comparative. Data got from BBC Indonesia on October 2014.The result shows that verb in Indonesian language based on past tenses using â€˜sudah/telahâ€™ before verb. In English language there are suffixes on the verb by using â€“ed or have/has/had before verb 3. The form of verb based on present tense, Indonesian language uses â€˜sedangâ€™ before verb while English language uses suffixes -ing. Based on future tense, Indonesian language uses â€˜akanâ€™ while English uses â€˜wilâ€™l before verb 1. Based on number, there is no change whether the subject singular or plural in Indonesian language. Both of verb in Indonesian and Ebglish language has the same position in syntactica, it is after subject of the sentence. While it will be different in English language, verb changed based on singular or plural number in different tenses. Based on equivalence, the translator uses formal and dynamic equivalence on verb.  Key Words : Contrastive Analysis, Verb, Tense, Number, andEquivalence of Translation